Biochemistry, pathology, and genetics of pulmonary emphysema : proceedings of an international symposium held in Sassari, Italy, 27-30 April 1980 - Bignon, Jean; Scarpa, G. L. (Giovanni Luigi) (Pergamon Press, 1981)
Biochemistry, Pathology and Genetics of Pulmonary Emphysema.